An Audit of Social Circumstances Reports for First-tier Tribunals in a Secure Psychiatric Service. Issue 4 (7th August 2016) - Haw, Camilla; Shears, Jane
Abstract : Social workers play a critical role in assisting Mental Health Tribunal panels to decide whether or not people detained as psychiatric inpatients could be discharged from their detention. The required structure and content of tribunal reports is laid down in Practice Directions, the most recent of which was published in October 2013 by the Courts and Tribunals Judiciary. The study aims were to audit the quality of social circumstances reports prepared for service users at a secure psychiatric hospital before and after the introduction of this Practice Direction and to see if a new report-writing template improved report quality. Eighty reports were audited in 2013 and a further 80 in 2014 against 28 key items derived from the Practice Direction. Reports prepared in 2013 contained on average 13.1 of 28 key items increasing to 19.1 in 2014. The template was used for 60% of reports in 2014 and resulted in better quality reports. In the repeat audit, more reports contained recommendations, mostly advising the service user's continued detention, though a few recommended discharge to a less restrictive placement. Such professional judgements take place at the juxtaposition of the Mental Health Act (1983) and the Human Rights Act (1998), in which risk management and risk-taking are key to decision-making.